Music intervention alleviates pain and distress in children undergoing vaccination: a systematic review and meta-analysis - Wang, Dan; Lei, Jiao; Wu, Shanshan; Zou, Zhuan; Li, Yang; Han, Jinbiao (Frontiers in Pediatrics, 2025)
ObjectivesTo systematically evaluate the efficacy of music intervention in reducing pain and distress among children during vaccination, addressing gaps in fragmented existing evidence.MethodsFollowing PRISMA guidelines, we searched PubMed, Embase, Cochrane Library, and Web of Science (inception to May 2024) for randomized controlled trials (RCTs) comparing music intervention with routine care in children (0–12 years) undergoing vaccination. Pain and distress were measured via validated scales. Two reviewers independently conducted study selection, data extraction, and risk-of-bias assessment (Cochrane RoB 1.0 tool). Meta-analysis was performed using Stata 17.0, calculating the standardized mean difference (SMD) and 95% confidence intervals (CI) with a random-effects model. Heterogeneity and sensitivity analyses were also performed.ResultsFive RCTs (306 children, 158 boys) from Turkey, the USA, Italy, and Iran were included. Participant ages ranged from infancy to 6 years. Music interventions varied in type (e.g., lullabies, children's songs) and duration. Music intervention significantly reduced both pain (SMD = –0.58, 95% CI: −0.92 to −0.24, I2 = 20.7%, p < 0.001) and distress (SMD = –0.83, 95% CI: −1.12 to −0.54, I2 = 38.1%, p < 0.001). Sensitivity analyses confirmed the robustness of these findings, and most studies had a low risk of bias.ConclusionMusic intervention may be an effective, safe, low-cost non-pharmacological strategy to alleviate pediatric vaccination-related pain and distress, supporting its integration into clinical practice.Systematic Review RegistrationPROSPERO CRD420251132834.